2011
DOI: 10.1590/s1807-59322011001200001
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial evaluating early versus traditional oral feeding after colorectal surgery

Abstract: OBJECTIVE:This prospective randomized clinical study was conducted to evaluate the safety and tolerability of early oral feeding after colorectal operations.METHODS:A total of 199 patients underwent colorectal surgery and were randomly assigned to early feeding (n = 99) or a regular diet (n = 100). Patients' characteristics, diagnoses, surgical procedures, comorbidity, bowel movements, defecation, nasogastric tube reinsertion, time of tolerance of solid diet, complications, and length of hospitalization were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 29 publications
7
71
0
5
Order By: Relevance
“…[6][7][8] Most of the practicing surgeon even today practicing, keep the patient NPO for 4-5 days after ileostomy closure and uses nasogastric tubes until resolution of the post operative ileus .Recently ,this approach has been questioned and few studies have shown that nasogastric tube insertion has a limited role in postoperative care of abdominal surgery. 2 In present study ,nasogastric tube was inserted before surgery and removed after 6 hr of surgery and this approach was tolerated by all the patients and in no patients we needed reinsertion of nasogastric tube.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…[6][7][8] Most of the practicing surgeon even today practicing, keep the patient NPO for 4-5 days after ileostomy closure and uses nasogastric tubes until resolution of the post operative ileus .Recently ,this approach has been questioned and few studies have shown that nasogastric tube insertion has a limited role in postoperative care of abdominal surgery. 2 In present study ,nasogastric tube was inserted before surgery and removed after 6 hr of surgery and this approach was tolerated by all the patients and in no patients we needed reinsertion of nasogastric tube.…”
Section: Discussionmentioning
confidence: 75%
“…3 Post operative starvation changes the metabolism of the body within 24 hours by increasing insulin resistance and reducing muscle function. 2 The purpose of this study is to evaluate that early feeding is having any additional advantage over the traditional feeding in terms of post operative ileus, bowel anastomosis leakage and hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…According to the reviewed studies, although the tolerance of the patient to the resumption of the diet is not universal, it is generally high [85][86][87] The use of nutritional strategies, including the prescription of oral supplements in the postoperative period and after discharge from patients undergoing major operations, can prevent complications and reduce the chances of readmission 130,131 . This is especially important in elderly patients 132 .…”
Section: Howmentioning
confidence: 99%
“…The mean age of the included patients was between 16 and 94 years (5,8), except one of them (16) that had a small group of children of 10 years, whom were not considered in this revision and only adults were included in the review. Men were more predominant within 18 (66.6%) of the studies (10)(11)(12)(13)(14)(17)(18)(19)(20)22,23,(25)(26)(27)(28)(29)(30)(31) and there was no mention about sex proportion in 2 (7.4%) works (6,8). Most of the studies proposed 2 groups, the intervention group (fast-track, G-FT) and the control group (traditional, G-T), only in 2 works 4 groups were designed (22,28) (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…The postoperative follow-up varied by time and used method ranging from a minimum of 3 postoperative days (POD) and a maximum of 29 POD (8,11,12,(15)(16)(17)19,22,27), only on author didn't mention the total follow-up period (9). The most of the authors monitored their patients even though others didn't mention It (5)(6)(7)13,14,23,25,28,29). Sometimes the follow-up was performed twice a day (9,12) while in another occasions a telephonic follow-up was used (10,18,21,24,27,30), those that reported the duration of follow-up period extended it until the 7 th POD or until patient hospital discharge (31).…”
Section: Resultsmentioning
confidence: 99%